Математическое моделирование металлургических процессов: учебное пособие - Александров С. Е. Сергей Евгеньевич; Голод В. М. Валерий Михайлович; Лунев В. А. Владимир Алексеевич; Федотов Б. В. Борис Фладимирович (Ленинград, ЛПИ, 1988)
Исключено из фонда НТБ ТПУ